Bidentate Lewis bases are preferred for passivation of MAPbI3 surfaces: A time-domain ab initio analysis. (January 2021) - He, Jinlu; Fang, Wei-Hai; Long, Run; Prezhdo, Oleg V.
Abstract: Chemical passivation is a predominant approach to inhibit intrinsic defects responsible for electron–hole recombination in perovskite solar cells. Using time-domain density functional theory combined with nonadiabatic molecular dynamics, we demonstrate defect passivation by separation of electrons and holes in metal halide perovskites (MHPs), and show that bidentate ligands exhibit the best performance. Defects in traditional semiconductors create deep midgap states, and passivation eliminates these states. In contrast, common defects produce no deep midgap states in MHPs. Instead, defects localize electrons and holes around defect sites, enhancing electron–hole interaction. Defect passivation in MHPs acts to separate charges, decreasing electron–hole and charge–phonon interactions, and increasing charge lifetimes. Bidentate ligands work best, because they can passivate both unsaturated chemical bonds created due to vacancy defects. Bidentate ligands with spatially separated binding sites are preferred, since they provide better match to the sparse inorganic lattice of MHPs. Similar to the Lewis base ligands, water also acts as a ligand and extends charge lifetimes, with the oxygen atom donating its lone electron pair to the defect site. However, water accelerates chemical degradation of MHPs. The binding energy of most ligands is larger than that of water, and therefore, the ligands displace water, increase MHP stability and prolong carrier lifetimes. The established physical mechanism of defect passivation, and the specific principles guiding the choice of passivating molecules advance our understanding of the exceptional properties of MHPs and suggest routes for further improvement of MHP performance in solar energy and optoelectronic applications. Graphical Abstract: Passivating defects with bidentate ligands is better than monodentate ligands in perovskite. ga1 Highlights: Binding of water and Lewis bases to I vacancies on CH3NH3PbI3 surface separates and extends lifetime of electrons and holes. Monodentate water, thiophene and pyridine passivate one under-coordinated Pb, while bidentate 2-MP and D4TBP passivate both. Charge recombination is driven by slow Pb-I vibrations. Quantum coherence is extremely short, favoring long-lived charges. The state-of-the-art simulation combines non-adiabatic molecular dynamics and time-domain density functional theory.